Simultaneous Quantification of γ-Hydroxybutyrate, γ-Butyrolactone, and 1,4-Butanediol in Four Kinds of Beverages - Shaoming Jin; Xiao Ning; Jin Cao; Yaonan Wang (International Journal of Analytical Chemistry)
γ-Hydroxybutyrate (GHB) is a neurotransmitter, which exhibits a strong central nervous system depressant effect. The abuse of GHB or its precursor substances (γ-butyrolactone (GBL) and 1,4-butanediol (1,4-BD)) may cause serious problems. This study developed a fast and effective UHPLC-MS/MS method for the simultaneous quantification of GHB, GBL, and 1,4-BD in four popular beverages, including carbonated drinks, tea, apple cider vinegar, and coffee. The established method overcomes the influence of the in-source collision-induced dissociation of unstable compounds during quantification. The limits of detection were 0.2 μg/mL for GBL and 0.5 μg/mL for GHB and 1,4-BD with excellent linearity in the range of 0.2–50 μg/mL. The recoveries of the three compounds at three spiked levels (2.5, 5.0, and 10.0 μg/mL) in the four kinds of beverages studied were between 90 and 110%, while the relative standard deviations (RSDs) were all <10%. The matrix effect was negligible using this simple and appropriate preprocessed procedure. The method established in this study can quickly and reliably detect the GHB content and its analogues in beverages.